2015
DOI: 10.1590/0104-1428.1924
|View full text |Cite
|
Sign up to set email alerts
|

Rheological, mechanical and morphological properties of poly(methyl methacrylate)/poly(ethylene terephthalate) blend with dual reactive interfacial compatibilization

Abstract: SbstractIn this work, the rheological, mechanical and morphological behavior of immiscible blend poly (methyl methacrylate) with elastomeric particles (PMMA elast ) and post-consumer poly (ethylene terephthalate) (PET) with and without the use of the interfacial compatibilizer poly (methyl methacrylate-co-glycidyl methacrylate-co-ethyl acrylate) (MGE) was studied. The significant increase in torque presented in rheological analyses has shown a indication of chemical reactions between the epoxy group of MGE wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…(30 wt% of PET). This corroborates with the efficiency results of the dual reactive interfacial compatibilization of PMMA elast /PET blend with MGE 16 . According to other researchers 25 , the compatibilization mechanism involves the induction of interfacial interactions between the components of the polymer blend.…”
Section: Microrheology Of the Pmma Elast /Pet And Pmma Elast /Pet/mgesupporting
confidence: 89%
See 1 more Smart Citation
“…(30 wt% of PET). This corroborates with the efficiency results of the dual reactive interfacial compatibilization of PMMA elast /PET blend with MGE 16 . According to other researchers 25 , the compatibilization mechanism involves the induction of interfacial interactions between the components of the polymer blend.…”
Section: Microrheology Of the Pmma Elast /Pet And Pmma Elast /Pet/mgesupporting
confidence: 89%
“…Poly (methyl methacrylate) with elastomeric particles (PMMA elast ) 13,14 and PET have complementary properties 15 ; hence, variations in the composition of their mixtures alter their structural and morphological characteristics. Earlier studies of PMMA elast /PET immiscible polymer blends conducted by Reinaldo et al 16 revealed synergistic properties that can be used in specific applications. As for the efficiency of compatibilization, the authors found evidence of dual reactivity between MGE and PET, and also with PMMA elast , due to the presence of the elastomer phase of PMMA.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its mechanical improvement compared to commercial homopolymer DOI: 10.1002/masy.202000153 poly(methyl methacrylate) (PMMAh), it has high potential for several technological applications. [1][2][3][4][5][6][7] Polycarbonate (PC) is an engineering polymer used in several applications due to its excellent mechanical properties, durability, transparency and thermal resistance. [8][9][10] Study of PMMAh/PC blend has mainly focused on the development of products for applications such as gas separation membranes, storage disks and packaging, due to its improvement on optical, thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The physical mixing of PMMAe with PC results in a synergistic combination of properties, since the use of this type of PMMA provides a complex mixing system due to the presence elastomeric particles, which produce properties different from those observed in PMMA/PC blends. Reinaldo et al used PMMAe for the development of polymer blend containing polyethylene terephthalate and achieved a synergistic combination of rheological, mechanical, and morphological properties, enabling the use of these polymer blends for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, some transparent and toughened PMMA materials with core‐shell particles are currently marketed as the elastomeric PMMA (PMMAe). This PMMAe is investigated in this study, and it can be used in many technological applications, partly because of its better mechanical performance than other commercial PMMA materials . Polycarbonate (PC) is used in a wide range of industrial applications due to its characteristic properties, such as high durability, excellent mechanical properties including impact strength and elastic modulus, high thermal resistance, and high transparency …”
Section: Introductionmentioning
confidence: 99%